URGENSI PEMASARAN DALAM PENINGKATAN PENERIMAAN SISWA BARU - Sunardi, Sunardi; Rino, Rino (ILJ: Islamic Learning Journal, 2023)
Competition in the world of education is inevitable, not a few educational institutions neglect their customers. The ability of an administrator to understand educational marketing is a prerequisite for the continuity and growth of his institution. This research is a qualitative study with data collection methods of documentation, observation and interviews, with descriptive analysis. The results stated that the implementation of marketing management is the main point of a school institution to promote the school and to get the expected prospective students. The distribution of promotional media tools in this school is done through calendars, brochures, banners, pamphlets, student guardians, online media such as Facebook, Instagram, and WhatsApp stories, for schools, cost is not a barrier to seeking knowledge, all circles can enter and no one objects.